A PRAGMATICS ANALYSIS OF SPEECH ACT IN THOR MOVIE - Tri Lestari; Elysa Hartati (Universitas PGRI Yogyakarta, 2017)
This research analyzed speech act which were expressed by Thor as the main character in Thor movie. That movie showed a candidate of king who was banished by his father because of his arrogant characteristic, so, there were many speech act which represented real life. Considering there are problems in English language learning focusing on speech act, so this study was conducted used pragmatics analysis. The purposes of this study were to classify speech act based on Searle’s theory and analyze speech act which has relation between the form and the function of the sentence.This research used descriptive qualitative method. The data which were used in this research were the utterances that were performed by the main character in the movie. The data analysis used pragmatics approach with theory by Searle. From the theory, there are 5 classifications of speech act, representative, directive, commissive, expressive, and declarative. There are 2 types of speech act which is discussed by Searle, direct and indirect.Based on the analysis, the researcher found that from the 5 classifications only 4 of them which were expressed by the main character, representative, directive, commissive, and expressive. Representative and directive were expressed 56 times each of them. Commissive appeared 20 times and expressive appeared 29 times. All types of speech act were expressed by the main character in the movie. Direct speech act were expressed 140 times, and indirect speech act were expressed 11 times.